2009
DOI: 10.3390/ijerph6010400
|View full text |Cite
|
Sign up to set email alerts
|

Bloodborne Viral Hepatitis Infections among Drug Users: The Role of Vaccination

Abstract: Drug use is a prevalent world-wide phenomenon and hepatitis virus infections are traditionally a major health problem among drug users (DUs). HBV and HCV, and to a lesser extent HAV, are easily transmitted through exposure to infected blood and body fluids. Viral hepatitis is not inevitable for DUs. Licensed vaccines are available for hepatitis A and hepatitis B. The purpose of this overview is to show some epidemiological data about HBV and the other blood-borne viral hepatitis among DUs and to summarize and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 80 publications
0
22
0
2
Order By: Relevance
“…HBV vaccination completion rates were high among groups of non-MM treatment drug users attending public health drug treatment centers in Italy (Quaglio et al, 2002). Other investigators have examined the impact of vaccine completion among persons who are enrolled in MM programs and have suggested that MM programs are an ideal place to provide HBV vaccination as these settings require frequent attendance (Lugoboni, Quaglio, Civitelli, & Mezzelani, 2009). For example, Borg et al (1999) reported a compliance rate of 86% for all three HBV doses among MM clinic attendees in New York City.…”
Section: Vaccination Compliancementioning
confidence: 99%
“…HBV vaccination completion rates were high among groups of non-MM treatment drug users attending public health drug treatment centers in Italy (Quaglio et al, 2002). Other investigators have examined the impact of vaccine completion among persons who are enrolled in MM programs and have suggested that MM programs are an ideal place to provide HBV vaccination as these settings require frequent attendance (Lugoboni, Quaglio, Civitelli, & Mezzelani, 2009). For example, Borg et al (1999) reported a compliance rate of 86% for all three HBV doses among MM clinic attendees in New York City.…”
Section: Vaccination Compliancementioning
confidence: 99%
“…While injecting drug use is the leading exposure category for notifications of newly acquired hepatitis B virus (HBV) infection in Australia 1 and vaccination is recommended for high-risk adults including people who inject drugs (PWID), 2 HBV immunization coverage in this group remains low. 3 This is despite the availability of a safe and effective vaccine being available free-of-charge for PWID in a range of clinical settings. Although the hepatitis B vaccine was included in Australia's infant vaccination schedule for 2000 with coverage reaching 86% of 1-year-old children in 2002, 4 universal infant vaccination will not impact on the immunity of Australia's adult populations for several decades.…”
Section: Introductionmentioning
confidence: 99%
“…Os usuários de drogas ilícitas apresentam elevado risco de adquirir microrganismos por meio de contato com sangue e/ou por relações sexuais desprotegidas (ALTER 2003;LUGOBONI et al, 2009;STRATHDEE & STOCKMAN, 2010 , 2009). No Sudeste do Brasil, prevalência relativamente semelhante (12,9%) foi observada entre usuários de drogas ilícitas no Rio de Janeiro (BASTOS et al, 2000).…”
Section: Discussionunclassified